A salbutamol fast-dissolving tablet based on freeze-drying-microsphere embedding technology and a preparation process thereof
Patent Information
- Application Number
- CN202510773278.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2045-06-11
AI Technical Summary
[0003]掩味效果不足——沙丁胺醇的强烈苦味导致患者(尤其儿童)依从性低下,常规冻干片在口腔崩解时药物直接接触味蕾,现有掩味技术如聚合物包衣会延长崩解时间至30秒以上,违背速溶片设计初衷;稳定性缺陷——冻干片的高孔隙率结构易吸湿,加速试验中水分吸附促使药物降解,导致有关物质超标(通常>1.5%),且含量均匀度因冻干过程药物迁移而波动(RSD>6%);工艺安全性风险——部分采用微球包埋的改进工艺依赖有机溶剂(如二氯甲烷)去除残留,存在毒理学隐患,不符合ICH对遗传毒性杂质限值要求
[0021]本发明通过透明质酸锌-普鲁兰多糖微球与梯度冷冻干燥协同作用,实现多重优势:首先,微球孔隙率75-85%结合普鲁兰多糖超高溶解度(200g/100mL),使崩解时间缩短至8秒内,5分钟溶出度达90%以上,显著优于传统冻干片(崩解>12秒,溶出<85%),满足哮喘急救需求;其次,锌离子与沙丁胺醇氨基形成配位键,通过阻断苦味受体T2R4(抑制率73.5%)及延迟药物接触舌面至崩解后5秒(离体猪舌模型验证),将苦味评分从传统制剂4.1分降至1.2分,儿童用药接受率提升至92%(市售片仅61%);第三,山梨醇-聚维酮K30复合物形成高Tg玻璃态基质(DSC测Tg=82℃),联合梯度干燥控制残留水分≤1.5%,使加速6个月有关物质增长≤0.5%(传统工艺>1.5%),水分吸附率降低3倍;第四,全程水性工艺消除有机溶剂残留,符合ICH Q3C安全标准,且微球包封率提升至98.2%(海藻酸钠体系仅91.5%);第五,微球密度(1.35g/cm3)大于唾液,确保96.3%舌下滞留,起效时间快至3.2分钟(口服液需10.5分钟),同时与除湿剂共包装(水蒸气透过率≤0.01g/(m2·day))解决冻干片吸湿难题。该技术可扩展至其他苦味碱性药物(log P<1),兼具工业化可行性。
Smart Images

Figure CN120549878B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the pharmaceutical field, and specifically discloses a salbutamol instant tablet based on freeze-drying-microsphere encapsulation technology and its preparation process. Background Technology
[0002] Salbutamol, as a β2 receptor agonist, is a key drug for treating asthma and chronic obstructive pulmonary disease (COPD). Its fast-dissolving tablets have attracted considerable attention due to their water-free administration and rapid onset of action. Current technologies primarily utilize freeze-drying processes to prepare porous structures for rapid disintegration, but this approach has significant drawbacks:
[0003] Insufficient taste masking effect – The strong bitterness of salbutamol leads to low patient compliance (especially in children). Conventional lyophilized tablets disintegrate directly in the mouth, and existing taste masking technologies such as polymer coating prolong disintegration time to over 30 seconds, contradicting the original design intent of fast-dissolving tablets. Stability defects – The high porosity of lyophilized tablets makes them prone to hygroscopicity, accelerating moisture adsorption during testing and promoting drug degradation, resulting in excessive levels of related substances (typically >1.5%). Furthermore, content uniformity fluctuates due to drug migration during lyophilization (RSD >6%). Process safety risks – Some improved processes using microsphere encapsulation rely on organic solvents (such as dichloromethane) to remove residues, posing toxicological risks and failing to meet ICH limits for genotoxic impurities. In addition, while existing microsphere material combinations (such as sodium alginate-chitosan) can improve encapsulation efficiency, chitosan's solubility drops sharply at physiological pH, resulting in insufficient drug release (dissolution rate <80% at 5 minutes). Moreover, these material combinations lack innovation due to their widespread use in sustained-release systems. The aforementioned defects collectively make it difficult for existing instant tablets to meet the core requirements of emergency medications for immediate onset of action, palatable taste, and long-term stability, thus necessitating the development of new dosage forms that combine technological innovation with clinical applicability. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a salbutamol instant tablet based on freeze-drying-microsphere encapsulation technology and its preparation process.
[0005] This invention includes the following technical solutions:
[0006] A fast-dissolving salbutamol tablet based on freeze-drying-microsphere encapsulation technology comprises a freeze-dried porous matrix and salbutamol-loaded microspheres dispersed therein. The microspheres are composed of zinc hyaluronic acid and pullulan polysaccharide through ionic cross-linking, with a mass ratio of 1:0.5-1:3. Principle: Microspheres are formed using ionic cross-linking to achieve drug encapsulation; Advantages: Improved drug stability and controlled release rate.
[0007] Furthermore, in the aforementioned tablets, the microspheres have a diameter of 20-150 μm, a porosity of 75-85%, and a zinc ion content accounting for 0.5-5% of the total weight of the microspheres. Principle: Optimizing microsphere size and porosity to control zinc ion content; Advantages: Improving drug dissolution and bioavailability while leveraging the auxiliary effect of zinc ions.
[0008] Furthermore, in the aforementioned tablets, the porous matrix contains a lyophilization protectant composed of sorbitol and povidone K30 in a mass ratio of 3:1-6:1, accounting for 8-12% of the porous matrix. Principle: The lyophilization protectant prevents the drug from becoming inactive during the freeze-drying process; Advantages: Protects drug activity and improves tablet stability.
[0009] Furthermore, the above-mentioned tablets exhibit a release rate of ≥90% after 5 minutes of in vitro dissolution and a disintegration time of ≤8 seconds. Principle: Optimized tablet composition and preparation process; Advantages: Achieves rapid dissolution and disintegration, improving the onset of drug action.
[0010] Furthermore, the above tablets were subjected to accelerated testing for 6 months under conditions of 40°C / 75% RH:
[0011] The growth rate of relevant substances is ≤0.5%;
[0012] Bitterness score ≤ 1.5, based on a 0-5 scale. Principle: By optimizing tablet composition and manufacturing process, drug stability is improved, and bitterness is reduced. Advantages: Extends drug shelf life and improves patient compliance.
[0013] The present invention also discloses a process for preparing the above-mentioned tablets, comprising the following steps:
[0014] (a) Dissolve salbutamol and zinc hyaluronic acid in acetate buffer, and add dropwise a solution containing 0.5-2 mM Ca. 2+ Microspheres are formed in pullulan polysaccharide solution; Principle: Microspheres are formed by ionic cross-linking reaction; Advantages: Effective encapsulation of drugs and improvement of drug stability.
[0015] (b) After being rapidly frozen in liquid nitrogen, the microspheres are pre-frozen at -45°C for 2-4 hours; Principle: The microsphere structure is maintained through rapid freezing and pre-freezing treatment; Advantage: It prevents the microspheres from breaking during freeze-drying and maintains the drug activity.
[0016] (c) Vacuum gradient drying: -35℃ / 3h → -15℃ / 4h → 10℃ / 2h → 25℃ / 3h, vacuum degree ≤5Pa. Principle: Gradient drying avoids damage to the microsphere structure, and the vacuum environment prevents oxidation; Advantages: Maintains the microsphere structure and drug activity, and improves tablet quality.
[0017] Furthermore, in the above process, the ionic strength of the acetate buffer solution in step (a) is 0.05-0.1M, and the microsphere cross-linking time is 10-30 minutes. Principle: Optimizing ionic strength and cross-linking time controls microsphere formation; Advantages: Obtaining uniform and stable microspheres improves drug encapsulation efficiency.
[0018] This invention also discloses the application of the above-mentioned tablets in the preparation of a sublingually soluble formulation for pediatric asthma, characterized in that each tablet contains 0.5-1.5 mg of salbutamol and 0.5-1 mg of sucralose per tablet. Principle: Optimizing drug content and adding sweeteners; Advantages: Suitable for children, improving patient compliance.
[0019] This invention also discloses the application of the above-mentioned tablets in the preparation of exercise-induced asthma emergency kits, characterized in that the tablets and desiccant are placed together in an aluminum-plastic blister pack, with a water vapor transmission rate ≤0.01g / (m²). 2 •day). Principle: Utilizes desiccant and aluminum-plastic blister packs to prevent tablets from getting damp; Advantages: Maintains tablet dryness and stability, suitable for emergency use.
[0020] Compared with the prior art, the present invention has the following outstanding advantages:
[0021] This invention achieves multiple advantages through the synergistic effect of zinc hyaluronic acid-pullulan polysaccharide microspheres and gradient freeze-drying: First, the microsphere porosity of 75-85% combined with the ultra-high solubility of pullulan polysaccharide (200g / 100mL) shortens the disintegration time to within 8 seconds, and the dissolution rate reaches over 90% within 5 minutes, significantly superior to traditional freeze-dried tablets (disintegration >12 seconds, dissolution <85%), meeting the needs of asthma emergency treatment; Second, zinc ions form a coordination bond with the amino group of salbutamol, blocking the bitter taste receptor T2R4 (inhibition rate 73.5%) and delaying drug delivery. Within 5 seconds of contact with the tongue and subsequent disintegration (verified using an isolated pig tongue model), the bitterness score decreased from 4.1 to 1.2 in traditional formulations, increasing the pediatric acceptance rate to 92% (compared to only 61% for commercially available tablets); third, the sorbitol-povidone K30 complex forms a high-Tg glassy matrix (DSC measured Tg = 82℃), and combined with gradient drying to control residual moisture ≤1.5%, the growth of related substances after 6 months is ≤0.5% (compared to >1.5% in traditional processes), and the moisture adsorption rate is reduced by 3 times; fourth, the entire process is aqueous, eliminating residual organic solvents, meeting ICH Q3C safety standards, and increasing the microsphere encapsulation rate to 98.2% (compared to only 91.5% in sodium alginate systems); fifth, the microsphere density (1.35 g / cm³) is... 3 Larger than saliva, ensuring 96.3% sublingual retention, with an onset time as fast as 3.2 minutes (oral liquid requires 10.5 minutes), and co-packaged with a dehumidifier (water vapor permeability ≤0.01g / (m²)). 2This technology solves the moisture absorption problem of freeze-dried tablets. It can be extended to other bitter-tasting alkaline drugs (log P < 1), and is industrially feasible. Attached Figure Description
[0022] Figure 1 Comparison of tablet disintegration times (s);
[0023] Figure 2 Comparison of tablet dissolution (%) at 5 min;
[0024] Figure 3 Comparison of cumulative dissolution (%) of tablets over 15 minutes. Detailed Implementation
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Table 1 Raw Material List
[0027]
[0028]
[0029] Table 2 Instrument List
[0030]
[0031] Example 1
[0032] 1. Microsphere preparation:
[0033] Weigh 10 mg of salbutamol and 50 mg of zinc hyaluronic acid, dissolve them in 20 mL of acetate buffer (0.07 M, pH 4.5), and add the solution dropwise at a uniform rate to a 2% pullulan polysaccharide solution containing 1 mM CaCl2 using a 23 G needle (0.33 mm inner diameter). Stir magnetically (300 rpm) for 20 minutes to crosslink the microspheres. Filter through a 200-mesh sieve to collect the microspheres.
[0034] 2. Freeze-dried slurry:
[0035] Lyophilization protectant: 120 mg sorbitol + 30 mg povidone K30 (4:1) dissolved in 5 mL purified water
[0036] Add microspheres and disperse ultrasonically (200W power, 40kHz frequency, 10 minutes).
[0037] 3. Freeze-drying:
[0038] Dispense into a PTFE mold (8mm in diameter, 2mm in depth).
[0039] Pre-freezing: -45℃ for 3 hours
[0040] Vacuum drying (vacuum degree 3Pa):
[0041] Maintain at -35℃ for 3 hours → Increase to -15℃ at 0.8℃ / min and maintain for 4 hours → Increase to 10℃ at 1℃ / min and maintain for 2 hours → Increase to 25℃ at 0.5℃ / min and maintain for 3 hours.
[0042] Example 2
[0043] Zinc hyaluronic acid: pullulan = 1:0.5
[0044] The rest is the same as in Example 1.
[0045] Example 3
[0046] Sorbitol:Povidone K30 = 6:1
[0047] Total concentration 12%
[0048] The drying gradient was adjusted to: -35℃ / 4h → -15℃ / 3h → 10℃ / 3h → 25℃ / 2h. The rest was the same as in Example 1.
[0049] Example 4
[0050] Pediatric preparations.
[0051] Salbutamol 1mg / tablet
[0052] Add 0.8mg of sucralose.
[0053] The diameter of the microspheres is controlled at 40±5μm (to optimize tongue feel).
[0054] The rest is the same as in Example 1.
[0055] Example 5
[0056] Salbutamol 0.5mg / tablet
[0057] Acetate buffer ionic strength 0.05M
[0058] Crosslinking time: 10 minutes
[0059] The rest is the same as in Example 1.
[0060] Comparative Examples 1-5
[0061] The parameters for Comparative Examples 1-5 are shown in Table 3, and the remaining steps are the same as in Example 1.
[0062] Table 3 Comparative Examples 1-5 Parameters
[0063] Comparison 1 Microspheres: Sodium alginate - chitosan (1:1) Creative contrast of materials Comparison 2 Freeze-drying protectant: 15% mannitol alone Verification of the necessity of composite protective agents Comparison 3 One-step drying: -45℃→25℃ (5h) Proving the irreplaceability of gradient drying Comparison 4 Contains 0.1% dichloromethane to remove residue Highlighting the safety advantages of water-based processes Comparison 5 Commercially available salbutamol lyophilized tablets (Company A) Commercial product performance benchmarks
[0064] Test Example 1
[0065] Basic performance testing.
[0066] method:
[0067] Disintegration time:
[0068] According to Method 0931 of the 2020 edition of the Chinese Pharmacopoeia, the ZBS-6G intelligent disintegration apparatus was used.
[0069] Medium: 900 mL purified water, temperature 37.0 ± 0.5℃
[0070] Test standard: The time point at which the tablet completely passes through the sieve (2.0 mm mesh) is repeated 6 times.
[0071] Dissolution rate:
[0072] Method: Paddlewheel method (USP Apparatus II), rotation speed 50±1 rpm
[0073] Medium: pH 6.8 phosphate buffer (prepared according to pharmacopoeia), 500 mL
[0074] Sampling points: 5 / 10 / 15 minutes, filtration through a 0.45μm membrane.
[0075] Detection: HPLC (Agilent 1260), chromatographic conditions:
[0076] Column: C18 (4.6×150mm, 5μm)
[0077] Mobile phase: Acetonitrile-0.1% phosphoric acid (25:75)
[0078] Flow rate: 1.0 mL / min, detection wavelength: 276 nm
[0079] The results are shown in Table 4 and Figure 1-3 .
[0080] Table 4 Basic Performance Tests
[0081] Example 1 6.3±0.5 95.2±1.8% 99.1±0.5% Example 2 7.8±0.7 91.5±2.1% 98.3±0.7% Comparison 1 14.7±1.2 82.1±3.4% 90.2±1.9% Comparison 5 12.5±0.9 85.6±2.7% 94.8±1.2%
[0082] Analysis: Disintegration mechanism: The porosity of the microspheres in this invention (81.3%) is significantly higher than that of control 1 (75.4%), and the water permeation rate reaches 0.35 mL / s·cm. 2 (Comparison 1: 0.18 mL / s·cm) 2 This is the key to achieving a collapse time of ≤8 seconds.
[0083] Dissolution advantage: The high solubility of pullulan (200g / 100mL) causes the microspheres to disintegrate rapidly, resulting in a drug specific surface area of 4.5m². 2 / g (Comparison 1 is 2.8m) 2 / g), to promote rapid dissolution.
[0084] Test Example 2
[0085] Stability test
[0086] Acceleration conditions:
[0087] A constant temperature and humidity chamber (40±2℃ / 75±5%RH) was placed for 6 months.
[0088] Sampling points: 0 / 1 / 3 / 6 months
[0089] Related substances detection:
[0090] Impurity A (relative retention time 0.8) and impurity B (relative retention time 1.2) were determined by HPLC.
[0091] Calculation: (Total of impurity A + Total of impurity B) - Initial value = Growth value
[0092] Bitterness assessment:
[0093] Double-blind design: 10 healthy volunteers (half male and half female) were trained to identify the bitterness threshold of salbutamol. Scoring criteria: 0 points = tasteless, 1 point = slightly negligible, 2 points = perceptible but not unpleasant.
[0094] 3 points = noticeably bitter, 4 points = intensely bitter, 5 points = unbearable.
[0095] The results are shown in Table 5.
[0096] Table 5 Stability Test Results
[0097] Example 1 0.32% 1.2±0.3 +0.9% Example 3 0.41% 1.4±0.4 +1.2% Comparison 2 1.58% 3.8±0.6 +3.5% Comparison 3 2.01% 4.1±0.5 +5.2%
[0098] Analysis: The sorbitol-K30 complex forms a glassy structure (DSC measurement Tg = 82℃), which inhibits microsphere aggregation and drug migration.
[0099] The gradient drying process reduces residual moisture to ≤1.5% (compared to 5.2% in Comparison 3), minimizing hydrolysis and degradation.
[0100] Bitterness control: Zinc ions can form a stable complex with salbutamol amino groups, blocking drug release.
[0101] Test Example 3
[0102] Microsphere odor masking mechanism verification
[0103] Objective: To elucidate the bitterness-blocking mechanism of zinc ion-pullulan polysaccharide microspheres.
[0104] method:
[0105] Oral retention time:
[0106] Ex vivo pig tongue model (for use within 2 hours after slaughter)
[0107] Fluorescent label: Salbutamol-FITC (excitation 485nm / emission 520nm)
[0108] High-speed camera (1000fps) records the time of drug contact with the tongue surface.
[0109] Bitter taste receptor inhibition:
[0110] Cell model: HEK293 cells transfected with hT2R4 (ATCC CRL-1573)
[0111] Irritant: 10 μM salbutamol solution ± zinc microsphere extract
[0112] Detection: Fluo-4 AM calcium fluorescent probe; inhibition rate calculated as (1 - fluorescence intensity of experimental group / control group) × 100%.
[0113] Zinc ion release kinetics:
[0114] Simulated saliva release: 37℃, 50rpm, pH 6.8
[0115] Zinc concentration was determined by atomic absorption spectrometry (PerkinElmer PinAAcle 900T).
[0116] The results are shown in Table 6.
[0117] Table 6. Verification of the odor-masking mechanism of microspheres
[0118] Example 1 5.2±0.8 73.5% 0.18±0.03 Comparison 1 1.3±0.4 12.1% - Comparison 5 2.1±0.6 8.7% -
[0119] Analysis: Triple masking mechanism:
[0120] ① Physical barrier: Pullulan forms a hydrophilic gel layer, delaying drug release to 5 seconds (compared to 1.3 seconds for control 1).
[0121] ② Chemical blocking: Zinc ions reversibly bind to the Glu265 site of the bitter taste receptor T2R4;
[0122] ③ Taste modification: Zinc ions inhibit ATP release from taste buds
[0123] Clinical relevance: When the exposure time was >5 seconds, the bitterness score was negatively correlated with the time (r = -0.89, p < 0.01).
[0124] Test Example 4
[0125] Children's application performance
[0126] Objective: To verify the palatability and emergency treatment effect of the pediatric formulation.
[0127] method:
[0128] Acceptance test: Medication adherence was recorded in 50 children aged 5-12 with asthma.
[0129] Onset of action: Time required for 15% improvement in FEV1 as monitored by lung function.
[0130] Anti-swallowing test: External simulation of oral cavity retention position (CT 3D reconstruction)
[0131] The results are shown in Table 7.
[0132] Table 7 Performance of Children's Applications
[0133] Example 4 92% 3.2±0.8 96.3% Commercially available oral liquids 78% 10.5±1.2 - Commercially available regular films 61% 15.8±2.1 -
[0134] Analysis: Palatability advantage:
[0135] Microspheres with a diameter of 40μm optimize tongue feel (tactile score > 4 / 5).
[0136] Sucralose and zinc ions synergistically mask bitterness (sensory evaluation shows a 63% reduction in bitterness intensity).
[0137] Quick-acting mechanism:
[0138] Direct absorption via sublingual mucosa (enhanced by microsphere penetration)
[0139] Avoiding the first-pass effect (bioavailability 78% vs. oral liquid 45%)
[0140] Anti-swallowing design: Microsphere density (1.35g / cm³) 3 ) > Saliva (1.02g / cm 3 This ensures that 96% remains under the tongue.
[0141] Summary: 1) Disintegration performance: The disintegration time of Example 1 was 6.3±0.5 seconds (Chinese Pharmacopoeia 0931 method), significantly lower than that of commercially available products (12.5±0.9 seconds), and the dissolution rate reached 95.2±1.8% at 5 minutes; 2) Stability: After 6 months of accelerated testing at 40℃ / 75%RH, the increase in related substances was only 0.32%, and the bitterness score remained stable at 1.2±0.3 (double-blind test with 10 participants); 3) Taste masking mechanism: The isolated pig tongue model showed that the drug contact with the tongue surface was delayed to 5.2±0.8 seconds, and the HEK293 cell experiment confirmed that zinc ions inhibited the bitter taste receptor T2R4 by 73.5%; 4) Pediatric application: The acceptance rate of 50 asthmatic children was 92%, the onset time was 3.2±0.8 minutes (pulmonary function monitoring), and the sublingual retention rate was 96.3%.
[0142] It is worth noting that the above description of the embodiments focuses on illustrating the technical solution of the present invention, rather than precisely defining its scope of protection. Those skilled in the art should understand that appropriate adjustments and optimizations can be made based on the technical details disclosed in the embodiments of the present invention, or equivalent substitutions can be implemented for individual or even all technical elements. Such adjustments and substitutions will not deviate from the core essence of the technical solution of the present invention and should be included within the technical protection scope of the embodiments of the present invention. In short, the protection of the present invention should not be limited to the concrete presentation of the above embodiments, but broadly covers all equivalent changes and improvements that do not depart from its basic concept. In summary, the protection definition of the present invention should be based on the statement of the claims, and the above embodiments are only used as a reference guide for understanding the present invention.
Claims
1. A salbutamol instant tablet based on freeze-drying-microsphere encapsulation technology, characterized in that, The product comprises a freeze-dried porous matrix and salbutamol-loaded microspheres dispersed therein, wherein the microspheres are composed of zinc hyaluronic acid and pullulan polysaccharide through ionic cross-linking, with a mass ratio of 1:0.5-1:
3. The microspheres have a diameter of 20-150 μm, a porosity of 75-85%, and a zinc ion content of 0.5-5% of the total weight of the microspheres. The porous matrix contains a freeze-drying protectant composed of sorbitol and povidone K30 in a mass ratio of 3:1-6:1, accounting for 8-12% of the porous matrix. The tablets have an in vitro dissolution rate of ≥90% after 5 minutes and a disintegration time of ≤8 seconds. The tablets were subjected to an accelerated test over 6 months at 40°C / 75%RH: The increase in relevant substances is ≤0.5%; Bitterness score ≤ 1.5, based on a 0-5 scale; The preparation process of the above tablets includes the following steps: (a) Salbutamol and zinc hyaluronic acid were dissolved in acetate buffer and then added dropwise to pullulan polysaccharide solution containing 0.5-2 mM Ca²⁺ to form microspheres; (b) After being flash-frozen in liquid nitrogen, the microspheres are pre-frozen at -45°C for 2-4 hours; (c) Vacuum gradient drying: -35℃ / 3h → -15℃ / 4h → 10℃ / 2h → 25℃ / 3h, vacuum degree ≤5Pa; In step (a), the ionic strength of the acetate buffer solution is 0.05-0.1M, and the microsphere cross-linking time is 10-30 minutes.
2. The application of the tablet as described in claim 1 in the preparation of a fast-dissolving sublingual formulation for childhood asthma, characterized in that, Each tablet contains 0.5-1.5 mg of salbutamol and 0.5-1 mg of sucralose per tablet.
3. The application of the tablet as described in claim 1 in the preparation of an exercise-induced asthma emergency kit, characterized in that, The tablets and desiccant are placed together in an aluminum-plastic blister pack, with a water vapor permeability ≤0.01 g / (m²·day).
Citation Information
Patent Citations
Salbutamol sulfate tablets and preparation method thereof
CN112022819A
Solid dosage forms comprising pullulan
US20040156895A1